2019
DOI: 10.3390/agronomy9110678
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Forms of Application of Azospirillum brasilense Associated with Silicon Use on Wheat

Abstract: The use of biological techniques such as plant growth-promoting bacteria (PGPB) can represent a sustainable alternative for cereal growth in tropical areas. Research showing the potential for management practices which optimize PGPB inoculation is of utmost importance. This research was developed to investigate the potential use of Azospirillum brasilense in wheat cropping systems, as well as to assess the potential synergistic interactions between the beneficial use of silicon (Si), principally under abiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…The use of agroecological practices such as inoculation by plant growth-promoting bacteria (PGPB) can represent a sustainable alternative for increase nutrient use efficiency in tropical agriculture (Galindo et al, 2018a(Galindo et al, ,b, 2019aMartins et al, 2018). The use of these PGPB is growing, particularly in Latin America, for different crops (Souza et al, 2015;Martins et al, 2018;Galindo et al, 2019a). Several PGPB genera show association with different species of agricultural importance, such as Azospirillum, Bacillus and Pseudomonas (Zeffa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The use of agroecological practices such as inoculation by plant growth-promoting bacteria (PGPB) can represent a sustainable alternative for increase nutrient use efficiency in tropical agriculture (Galindo et al, 2018a(Galindo et al, ,b, 2019aMartins et al, 2018). The use of these PGPB is growing, particularly in Latin America, for different crops (Souza et al, 2015;Martins et al, 2018;Galindo et al, 2019a). Several PGPB genera show association with different species of agricultural importance, such as Azospirillum, Bacillus and Pseudomonas (Zeffa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Map created by using QGIS software and Google Earth program (http://qgis.osgeo.org) concluded the combined application of PGPR and Si amendment could be a feasible and effective approach to improve growth and salinity tolerance in coriander (Coriandrum sativum L.). Galindo et al (2019b) studied different A. brasilense inoculation methods combined with Ca and Mg silicate and reported that seed inoculation in combination with silicate application increased wheat grain yield by 6.7%. These results indicate a synergistic effect between A. brasilense inoculation and Si application on cereal grain yield.…”
Section: Core Ideasmentioning
confidence: 99%
“…Some studies have reported Si can be beneficial under biotic and abiotic conditions [71,72]. For example, Galindo et al [41] studying inoculation methods associated with Si application reported an average wheat grain yield increase of 6.7% when seed inoculation and Si application were performed. Guével et al [71] observed that foliar applications of three different Si products (Kasil 26.5% SiO 2 ; Silamol 2% SiO 2 and 46% K 2 O; and MRD-250 43.2% of SiO 2 ) did not promote wheat plant growth compared to the control treatment under greenhouse conditions, except when the plants were infected by powdery mildew.…”
Section: Plos Onementioning
confidence: 99%
“…Calcium and magnesium silicate also can increase base saturation and extractable levels of P, Ca, Mg, and Si, as well as decrease the phytotoxic effect of Fe, Mn, Zn, Al, and Cd [38,39] and correct soil acidity [40]. Galindo et al [41] studying inoculation methods associated with Si application reported an average wheat grain yield increase of 6.7% when seed inoculation and Si application were performed.…”
Section: Introductionmentioning
confidence: 99%